Molecular Detection of Cryptosporidium spp. and Enterocytozoon bieneusi Infection in Wild Rodents From Six Provinces in China - Ni, Hong-Bo; Sun, Yu-Zhe; Qin, Si-Yuan; Wang, Yan-Chun; Zhao, Quan; Sun, Zheng-Yao; Zhang, Miao; Yang, Ding; Feng, Zhi-Hui; Guan, Zheng-Hao; Qiu, Hong-Yu; Wang, Hao-Xian; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Enterocytozoon (E.) bieneusi and Cryptosporidium spp. are the most important zoonotic enteric pathogens associated with diarrheal diseases in animals and humans. However, it is still not known whether E. bieneusi and Cryptosporidium spp. are carried by wild rodents in Shanxi, Guangxi, Zhejiang, Shandong, and Inner Mongolia, China. In the present study, a total of 536 feces samples were collected from Rattus (R.) norvegicus, Mus musculus, Spermophilus (S.) dauricus, and Lasiopodomys brandti in six provinces of China, and were detected by PCR amplification of the SSU rRNA gene of Cryptosporidium spp. and ITS gene of E. bieneusi from June 2017 to November 2020. Among 536 wild rodents, 62 (11.6%) and 18 (3.4%) samples were detected as E. bieneusi- and Cryptosporidium spp.-positive, respectively. Differential prevalence rates of E. bieneusi and Cryptosporidium spp. were found in different regions. E. bieneusi was more prevalent in R. norvegicus, whereas Cryptosporidium spp. was more frequently identified in S. dauricus. Sequence analysis indicated that three known Cryptosporidium species/genotypes (Cryptosporidium viatorum, Cryptosporidium felis, and Cryptosporidium sp. rat genotype II/III) and two uncertain Cryptosporidium species (Cryptosporidium sp. novel1 and Cryptosporidium sp. novel2) were present in the investigated wild rodents. Meanwhile, 5 known E. bieneusi genotypes (XJP-II, EbpC, EbpA, D, and NCF7) and 11 novel E. bieneusi genotypes (ZJR1 to ZJR7, GXM1, HLJC1, HLJC2, and SDR1) were also observed. This is the first report for existence of E. bieneusi and Cryptosporidium spp. in wild rodents in Shanxi, Guangxi, Zhejiang, and Shandong, China. The present study also demonstrated the existence of E. bieneusi and Cryptosporidium spp. in S. dauricus worldwide for the first time. This study not only provided the basic data for the distribution of E. bieneusi and Cryptosporidium genotypes/species, but also expanded the host range of the two parasites. Moreover, the zoonotic E. bieneusi and Cryptosporidium species/genotypes were identified in the present study, suggesting wild rodents are a potential source of human infections.